Proceso de atención de enfermería en paciente de 75 años con insuficiencia renal crónica. - Calderón Corte, Lucelly Fabiola (2020)
The following clinical case study is intended to treat chronic kidney disease (CKD) as a major public health problem. If they are not treated in time, they lead to greater complications for the patient, further affecting the health of the individual and even leading to death. CKD is considered the common final destination for a constellation of pathologies that affect the kidney chronically and irreversibly. Once the diagnostic and therapeutic measures for primary kidney disease have been exhausted, CKD entails common and generally independent action protocols. Nursing care for the patient is defined as a dynamic and systematic way of providing care focusing on the performance of nursing interventions, simple, easy to carry out and in the shortest time, it is essential for a good performance of nursing diagnoses. and care plans. In this work, detailed information is found on the 75-year-old male patient with lower limb edema, anorexia, thus becoming a vulnerable person since CKD if not treated in time can even cause death. Once the functional patterns were established, the nursing care plan was developed to provide quality care and warmth to the patient; Once the necessary diagnosis and treatment had been carried out, the patient's relatives were informed of the pathology, the causes, and the necessary treatment for his recovery, who demonstrated the desire to collaborate for his well-being.